Quantifying the effect of high-spin/low-spin crossover on electron d(5)d(5) M2Cl93- (M = Fe, Ru, Os) dimers - Stranger, R; Lovell, T; McGrady, J (2002)
Density functional theory has been used to investigate the effect of high-spin/low-spin crossover on the delocalization of metal-based electrons in homo- and hetero-bimetallic d5d5 face-shared M2Cl93- (M = Fe, Ru, Os) dimers. The energetic contributions of the ligand-field, ΔELF, spin-polarization, ΔEspe, and orbital overlap, ΔEovlp, terms to the high-spin/low-spin and localized/delocalized equilibria in these dimer systems have been quantified. The two equilibria are found to exhibit a strong linear dependence, which can be attributed to their connection with the single-ion spin-polarization energy. It can be concluded that metal-metal bond formation necessitates a crossover from a high-spin to low-spin configuration in these dimer systems, and, therefore, neither delocalized high-spin or localized low-spin d5d5 structures are likely to occur. © 2002 Elsevier Science Ltd. All rights reserved.